Why do consumers buy green apparel? The role of dispositional traits, environmental orientation, environmental knowledge, and monetary incentive. (September 2021) - Sadiq, Mohd; Bharti, Kumkum; Adil, Mohd; Singh, Ramendra
Abstract: This study investigates the influence of both consumer optimism and pessimism on the green apparel buying behavior, using the self-focused regulation theoretical framework. Further, it measures the mediation effect of environmental orientation, and the moderation effect of environmental knowledge and monetary incentive on the proposed associations. An online survey was conducted through Amazon Mechanical Turk to collect data from 450 consumers. The findings reveal that optimistic consumers buy green apparel, while pessimistic consumers avoid it. Interestingly, when environmental orientation is introduced as a mediator, the pessimistic consumers also express the intent to buy green apparel. Further, environmental knowledge and monetary incentive both significantly moderate the relationships of green apparel buying behavior with consumer pessimism and environmental orientation. Holistically, this study provides significant implications for both green apparel marketers and retailers. Highlights: The study investigates the influence of consumer optimism and consumer pessimism on green apparel buying behavior . Findings confirmed the existence of environmental orientation-behavior gap. Traits like pessimism is a significant barrier of green apparel buying behavior. Moderating role of environmental knowledge and monetary incentive are also investigated.